The Effect of NPM, DPR, DER and Existed Size of the Company Towards the Income Smoothing in Manufacturing Companies - Dara Sarra, Hustna; Mikrad, Mikrad (Dinasti Publisher, 2021)
Income smoothing is a natural thing to do by management because of fluctuations in income which are considered abnormal and sometimes not as in line as the stated plan of the company set up at the beginning. Financial reports published on the Indonesian Stock Exchange are usually always analysed by investors and potential investors as a basis for decision making, one way for investors to detect that the reports presented indicate high income smoothing values ??which can cause mistakes in decision making and harm. One way to detect the smoothing condition of the existed income is based on the index of Eckel standards of regulations. This study uses a population of 72, for 4 years in the manufacturing sector to companies used the index of Eckel standards of regulations by means of measuring the condition of smoothing of the income. The results showed that firm size had an effect on income smoothing while DER, NPM and DPR had no effect on income smoothing.